Calcite (104) Surface-Electrolyte Structure: A 3D Comparison of Surface X-ray Diffraction and Simulations - Brugman, S.J.T.; Raiteri, Paolo; Accordini, P.; Megens, F.; Gale, Julian; Vlieg, E. (AMER CHEMICAL SOC, 2020)
Adsorption and incorporation of ions are known to influence the morphology and growth of calcite. Using surface X-ray diffraction, the interfacial structure of calcite in contact with CaCO3, MgCl2, CaCl2, and BaCl2 solutions was determined. All of these conditions yield a comparable interfacial structure, meaning that there is no significant ion adsorption on the terraces under the investigated conditions. This allows, for the first time, a thorough comparison in all three dimensions with state-of-the-art computer simulations, involving molecular dynamics based on both density functional theory (DFT) and two different force field models. Additionally, the simulated structures are used to calculate the corresponding structure factors, which in turn are compared to those obtained from experiment, thereby avoiding the need for fitting or subjective interpretation. In general, there is a good agreement between experiment and the simulations, although there are some small discrepancies in the atomic positions, which lead to an inadequate fit of certain features characteristic of the structure of water at the interface. Of the three simulation methods examined, the DFT results were found to agree best with the experimental structure.